2011
DOI: 10.1128/jcm.05429-11
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Switch to Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry for Routine Bacterial Identification

Abstract: ᰔMatrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) allows instant identification of microorganisms by analyzing their total protein content (1-3). In September 2009, we switched from conventional biochemical techniques (mainly Vitek 2 and API strips) to MS (Microflex; Bruker Daltonics, Wissembourg, France) for routine identification of all bacterial isolates except for mycobacteria and mycoplasma. Conventional tests were only kept in case of equipment failure or mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 4 publications
1
37
1
Order By: Relevance
“…Matrixassisted laser desorption ionization-time of flight (MALDI-TOF) analysis is rapidly becoming a routinely used tool in many microbiology laboratories, whereby proteins liberated from bacteria are ionized and detected by a mass spectrometer (MS), the spectrum is analyzed, and its pattern is compared to entries found in a database, giving rise to a degree of match (1,29). This technology is touted as being revolutionary, because it does not require extensive training or expertise in MS or chemistry to use and the cost for consumables is described as less than US$0.50 per sample, excluding the cost of the MALDI-TOF instrument (21). Protein fingerprints are deemed to provide identification to genus and species with an accuracy which approaches that of genetic methods (1,29).…”
mentioning
confidence: 99%
“…Matrixassisted laser desorption ionization-time of flight (MALDI-TOF) analysis is rapidly becoming a routinely used tool in many microbiology laboratories, whereby proteins liberated from bacteria are ionized and detected by a mass spectrometer (MS), the spectrum is analyzed, and its pattern is compared to entries found in a database, giving rise to a degree of match (1,29). This technology is touted as being revolutionary, because it does not require extensive training or expertise in MS or chemistry to use and the cost for consumables is described as less than US$0.50 per sample, excluding the cost of the MALDI-TOF instrument (21). Protein fingerprints are deemed to provide identification to genus and species with an accuracy which approaches that of genetic methods (1,29).…”
mentioning
confidence: 99%
“…26 Further, MALDI-TOF is both cost and environmentally effective when compared with conventional microbiology. Gaillot et al 27 demonstrated 89.3% cost savings in the first year of MALDI-TOF use, whereby cost per isolate decreased from $5.80 to $0.50 and waste reduced from >1400 kg to <50 kg, in addition to lesser need for DNA and/or RNA sequencing and, overall, significantly enhanced time to bacterial identification. At the time of writing, microbiological testing at UHL was predominantly based on the bioMérieux ® ARIS system costing approximately €3.50 per identification, and with ca.…”
Section: Can Laboratory Results Be Expedited?mentioning
confidence: 99%
“…16 Most of these misidentifications can be attributed to an incomplete population of databases associated with the instrument. 1,7,18,21,22 For instance, it has recently been reported that improvements to the database enable a more reliable distinction between S. pneumoniae and viridans group streptococci. 23,24 Because the reference databases are not static and expanded regularly to fill in current gaps in identification, updates will continue to improve the performance of MALDI-TOF MS. 18 To the best of our knowledge, this study represents the first implementation and use of MALDI-TOF MS for the identification of bacteria and fungi in a hospital in tropical Africa.…”
Section: Discussionmentioning
confidence: 99%
“…1,6 Overall, it has been clearly shown that MALDI-TOF MS is less expensive than traditional methods, even when taking into account the costs of reagents, labor, performance measurements, waste disposal, microorganism prevalence, and instrument maintenance expenses as well as multiple runs and additional tests needed to maximize accuracy. 6,18,21,22 Moreover, several studies have shown the clinical benefits of using MALDI-TOF MS. This technique can provide microorganism identification up to 30 hours faster than conventional phenotypic methods; such gains in the speed of identification can have a substantial impact on patient care and management.…”
Section: Discussionmentioning
confidence: 99%